Var finner vi hopp? - Wiesel, Elie (Nordisk judaistik/Scandinavian Jewish Studies, 1991)
Where is hope to be found? Elie Wiesel tries to find traces of hope by exploring Jewish tradition, biblical examples and the nature of God. Wiesel finds that thankfulness is intrinsically connected to hope.